PENERAPAN (ROM) PASIF PADA LANSIA DENGAN GANGUAN MOBILITAS FISIK DI PANTI GRIYA JANATI - Hamna Vonny Lasanuddin; Sri Yulian Hunowu; Moh. Yusran Basri (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Introduction: Stroke is a major health problem for today's modern society. Today, stroke is becoming a serious problem worldwide. This is because a sudden stroke can result in death, physical and mental disability in productive and old age. Methods: This study used a qualitative approach with the case method. Sunberg (2007) explains that a case study is a report or narrative by a therapist about the treatment of a single client, even though the report could be about a family or a group. In addition, this study also uses "ABA Design" where A is the initial phase of the intervention (Baseline Phase), namely the target aspect of the behavior to be intervened, B is the treatment phase (Treatment Phase), which is the application of intervention techniques, then followed by A is the follow-up phase. follow-up phase, namely the phase of evaluating the progress of the intervention technique that has been given, and knowing whether the subject can maintain the behavior that has been intervened. Objective: to identify the muscle strength of stroke patients before and after ROM is carried out, and identify the effect of giving Range OF Motion (ROM) on muscle strength in stroke patients. Conclusion: The first patient, Mr. "S", motion exercises are more effective for the lower limbs or lower extremities, already able to be moved even though they are still assisted with activities, for the second patient Mrs. "V.S" complains of lower limbs or lower extremities, difficulty in doing activities , feeling dizzy, while for patient 3 Ny. "N.U" complained of dizziness, felt that his left limbs were weak and weak, had a history of stroke.